2014
DOI: 10.1159/000360699
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcomes for both Mother and Baby Are Possible in Pregnant Women with Crimean-Congo Hemorrhagic Fever Disease: A Case Series and Literature Review

Abstract: To assess the impact of Crimean-Congo hemorrhagic fever (CCHF) infection during pregnancy on maternal and fetal outcomes, we present the clinical and laboratory findings and outcomes of 5 pregnant women with CCHF infection as well as fetal outcomes. We also reviewed previously reported cases with CCHF infection in pregnant women. All pregnant women with CCHF infection who had been hospitalized between August 2007 and September 2011 were included. The gestational ages at the time of CCHF infection were 8, 18, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Here, we were only able to examine female reproductive tissues, so whether these findings extend to male reproductive tissues and any implications for sexual transmission remain to be determined. Several reports focused on CCHF in pregnant women and outcomes in neonates [34][35][36][37][38][39], but to date, there is only one report of potential sexual transmission [40]. Our data support future investigations into reproductive infection, pathology, and implications for CCHFV transmission, as well as using both female and male models of disease for these and other pathogenesis studies.…”
Section: Differential Cytokine Expression In Mice Infected With Eithesupporting
confidence: 74%
“…Here, we were only able to examine female reproductive tissues, so whether these findings extend to male reproductive tissues and any implications for sexual transmission remain to be determined. Several reports focused on CCHF in pregnant women and outcomes in neonates [34][35][36][37][38][39], but to date, there is only one report of potential sexual transmission [40]. Our data support future investigations into reproductive infection, pathology, and implications for CCHFV transmission, as well as using both female and male models of disease for these and other pathogenesis studies.…”
Section: Differential Cytokine Expression In Mice Infected With Eithesupporting
confidence: 74%
“…The most complete data set previously reported was by Gozel et al in 2014 who published a case series of 5 pregnant women with CCHF and summary data on 21 other reported cases 10 . Our systematic review identified an additional 7 reports (10 cases), that combined with our large additional case series provided a total 42 cases of CCHF in pregnancy for analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Viral hemorrhagic fevers such as Ebola virus disease and Lassa Fever are more severe in pregnancy,7, 8 and frequently result in spontaneous abortion with additional nosocomial risk. Although clinical and epidemiological CCHF data are increasingly reported, few data exist on CCHF in pregnancy 9, 10, 11. The mortality of CCHF disease in pregnant women appears to be higher than in the general population (up to 33%), 10 and the severe course of CCHF in pregnant women may also increase risk of nosocomial infection in health care settings 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Maternal mortality rate reached 34% in pregnant women with Crimean-Congo hemorrhagic fever, which is likely higher than in the general population. 48,49…”
Section: Maternal Clinical Presentationmentioning
confidence: 99%